METHODS OF CIVIL LEGAL PROTECTION OF INTELLECTUAL PROPERTY RIGHTS - To‘raboyeva Mahliyo Ozod qizi (Journals Park Publishing, 2024)
In this article, intellectual property rights, including methods of copyright protection, are studied on the basis of a comparative analysis of the legislation of the Republic of Uzbekistan and other foreign countries. Issues related to the protection of intellectual property rights were considered.
Keywords: Intellectual property rights, copyright, related rights, intellectual property protection, protection methods.